The Essence of Christianity - Sykes, Stephen (Religious studies, 1971)
The phrase 'essence of Christianity' is ambiguous. The basic reason for this is that the word 'essence' has a more natural, though by no means uncomplicated, reference to substances, whether in philosophical or pharmacological discussion. Outside such contexts the use of phrases like 'the heart of the matter', or the 'essence of happiness' sound like earnest, but rhetorical devices to commend the depth or fundamental character of a specific investigation.